Study of the Pre-existence of Christ According to the Jehovah’s Witnesses - Exson Pane (Fakultas Filsafat Universitas Advent Indonesia, 2021)
One of the foundational teaching in the history of Christianity is the existence of Christ. Mostly Christians believed that Christ already exist prior His incarnation. Jesus was with the Father, and Holy Spirit. They are co-exist , no beginning and no end, they are eternal from eternity to eternity. However, Arianism rejected the traditional view of the Christianity regarding Christ existence. The Arianism’s view regarding the pre-existence of Christ admired by the Jehovah’s Witnesses. Jehovah’s Witnesses believed that was exist prior to His incarnation but not co-exist with the Father. Christ is only begotten son of the Father as the first creation and Father endowed Christ the divinity.